Combining spatial planning and ecosystem services value to assist ecological compensation decision-making—A case study of Yangtze River Delta ecological barrier, China - Wang, Ziyi; Wang, Yu; Zhou, Zihang; Yu, Fan; Ma, Debin; Li, Jiaming (Frontiers in Environmental Science, 2022)
China’s ecological compensation (EC) is based on the property rights structure of public ownership of natural resources, which should be based on the spatial planning, which is defined by local government as the boundary of property right management and the distribution of development power. This study combined spatial planning and ecosystem service value (ESV) accounting to design a decision-making framework of EC, which includes “Subject choice, Value accounting, Priority evaluation, Policy supply”. We selected 32 counties (districts) in the Yangtze River Delta region as the research object with the consideration of spatial planning and expert advice, and found that the implementation of EC slowed down the urbanization process and promoted the increase of ecological space. We conducted an accounting and sensitivity analysis on the spatial and temporal changes of ESV in the region from 2000 to 2019, and finally determined the amount and priority of accepting EC. The research results show that the ESV in the study area shows a general trend of increasing and then decreasing in time, and a spatial pattern of high in the south and low in the north and high in the east and low in the west. Forestland and water area are the main providers of ESV in the study area. The sensitivity coefficients of each type of ESV do not change much in each period, but the coefficients between the types have large differences. The total amount of EC in the Yangtze River Delta ecological barrier (YRDEB) is RMB 38,098.11 billion, and Shitai County is the area with the highest priority for compensation. We believe that this decision-making framework has the potential to be applied to the implementation of EC in other regions of China. At the same time, it can also be used to enrich the international views on EC research.